Antenatal Training with Music and Maternal Talk Concurrently May Reduce Autistic-Like Behaviors at around 3 Years of Age - Ruan, Zeng-Liang; Liu, Li; Strodl, Esben; Fan, Li-Jun; Yin, Xiao-Na; Wen, Guo-Min; Sun, Deng-Li; Xian, Dan-Xia; Jiang, Hui; Jing, Jin; Jin, Yu; Wu, Chuan-An; et al. (Frontiers in Psychiatry, 2018)
Antenatal training through music and maternal talk to the unborn fetus is a topic of general interest for parents-to-be in China, but we still lack a comprehensive assessment of their effects on the development of autistic-like behaviors during early childhood. During 2014–2016, 34749 parents of children around the age of three years who were enrolled at kindergarten in the Longhua district of Shenzhen participated in this study. Self-administered questionnaires regarding demographics, antenatal music training and maternal talk to the fetus during pregnancy were completed by the children’s primary caregivers. Autistic-like behaviors were assessed using the Autism Behavioral Checklist. Tobit regression analyses revealed that antenatal music training and maternal talk to the fetus was associated with a reduction in autistic-like behaviors in children, with a dose-dependent relationship. Furthermore, factorial analysis of covariance indicated a significant interaction effect between antenatal music training and maternal talk to the fetus on the autistic-like behaviors, and found that children who often experienced antenatal music training and maternal talk concurrently had the lowest risk of autistic-like behaviors, while children who were never exposed to maternal talk and only sometimes experienced antenatal music training had the highest risk. Our results suggest that antenatal training through both music and maternal talk to the unborn fetus might reduce the risk of children’s autistic-like behaviors at around three years of age.